Derivatives and risk management - Madhumathi, R.; Ranganatham, M. (New Delhi : Pearson, 2011)
Through the incorporation of real-life examples from Indian organizations, Derivatives and Risk Management provides cutting-edge material comprising new and unique study tools and fresh, thought-provoking content. The organization of the text is designed to conceptually link a firm's actions to its value as determined in the derivatives market. It addresses the specific needs of Indian students and managers by successfully blending the best global derivatives and risk management practices with an in-depth coverage of the Indian environment.
Keywords: Derivatives; Risk Management